Salivary Microbiota and Host-Inflammatory Responses in Periodontitis Affected Individuals With and Without Rheumatoid Arthritis - Eriksson, Kaja; Lundmark, Anna; Delgado, Luis F.; Hu, Yue O. O.; Fei, Guozhong; Lee, Linkiat; Fei, Carina; Catrina, Anca I.; Jansson, Leif; Andersson, Anders F.; Yucel-Lindberg, Tülay (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: Periodontitis and rheumatoid arthritis (RA) are two widespread chronic inflammatory diseases with a previously suggested association. The objective of the current study was to compare the oral microbial composition and host´s inflammatory mediator profile of saliva samples obtained from subjects with periodontitis, with and without RA, as well as to predict biomarkers, of bacterial pathogens and/or inflammatory mediators, for classification of samples associated with periodontitis and RA. Methods: Salivary samples were obtained from 53 patients with periodontitis and RA and 48 non-RA individuals with periodontitis. The microbial composition was identified using 16S rRNA gene sequencing and compared across periodontitis patients with and without RA. Levels of inflammatory mediators were determined using a multiplex bead assay, compared between the groups and correlated to the microbial profile. The achieved data was analysed using PCoA, DESeq2 and two machine learning algorithms, OPLS-DA and sPLS-DA. Results: Differential abundance DESeq2 analyses showed that the four most highly enriched (log2 FC >20) amplicon sequence variants (ASVs) in the non-RA periodontitis group included Alloprevotella sp., Prevotella sp., Haemophilus sp., and Actinomyces sp. whereas Granulicatella sp., Veillonella sp., Megasphaera sp., and Fusobacterium nucleatum were the most highly enriched ASVs (log2 FC >20) in the RA group. OPLS-DA with log2 FC analyses demonstrated that the top ASVs with the highest importance included Vampirovibrio sp. (ASV1262) having a positive correlation with non-RA group, and seven ASVs (Sphingomonas insulae (ASV626), Sphingobium sp. (ASV435), Novosphingobium aromaticivorans (ASV668), Delftia acidovorans (ASV638), Aquabacterium sp. (ASV333), Aquabacterium sp. (ASV649), Sphingomonas echinoides (ASV993) with a positive correlation with RA group. Among the detected inflammatory mediators in saliva samples, TWEAK/TNFSF12, IL-35, IFN-α2, pentraxin-3, gp130/sIL6Rb, sIL-6Ra, IL-19 and sTNF-R1 were found to be significantly increased in patients with periodontitis and RA compared to non-RA group with periodontitis. Moreover, correlations between ASVs and inflammatory mediators using sPLS-DA analysis revealed that TWEAK/TNFSF12, pentraxin-3 and IL-19 were positively correlated with the ASVs Sphingobium sp., Acidovorax delafieldii, Novosphingobium sp., and Aquabacterium sp. Conclusion: Our results suggest that the combination of microbes and host inflammatory mediators could be more efficient for classification of RA and non-RA periodontitis, as compared to microbes alone.